Dictionaries of grammatical and morphological terms Lexical study in the light of contemporary linguistics - Allam, Eman Abdel-Jaber Abdel-Samie (Journal of Humanities & Social Sciences, 2020)
The topic (Dictionaries of grammatical and morphological terms, a lexical study in the light of contemporary linguistics) relates to the extent to which the mentioned dictionaries apply the rules of the modern lexicon industry in terms of introduction and construction of the lexicon.The research revealed that: The care of dictionaries studied with some rules of the introduction of dictionaries, the interest of those dictionaries in their major and minor structures.
Keywords: introductions to dictionaries; major structure; minor structure; lexical study